Depression, anxiety, and stress among adolescents in Kuantan and its association with religiosity-a pilot study - Mohamad, Ahmad Safwan; Draman, Samsul; Md Aris, Mohd Aznan; Musa, Ramli; Malik, Maszlee (2016)
Introduction: Adolescence is the period when the personality is developing. At this stage, the internal crisis has been playing a major role in the development of personality. Studies have shown that religiosity can affect the mental health of a person. This study is done to look at the association between religiosity and mental health in adolescents. Methodology: 50 questionaires paper have been distributed to 50 students who have consented for enrolment in the study, in a secondary school in Kuantan District. Only 41 papers are qualified to be analyzed by using SPSS Version 20. Result: The mean score for depression, anxiety, and stress are 5.83, 5.59, and 8.34 respectively. 43.9% of the respondents are moderately depressed, while only 24.4 percent are normal. The anxiety status of respondents shows that 22% are normal and moderately anxious, respectively. About 17% are extremely severe for anxiety. The status of stress shows that 31.7% are not stressed, while 24.4% are having severe stress. For religiosity, the mean score for Organized Religiosity (ORA) was 4.07, Non Organized religiosity (NORA) was 4.24, and Intrinsic religiosity (IR) was 12.66, which corresponds with the data from Santa Clara Strength of Religious Faith scale (SCSORF), which has the mean score of 35.3. Family income has shown to be negatively corresponding to the depression,anxiety, and stress. The religiosity has shown to be correlating negatively with depression and stress, but having positive correlation with anxiety. The reliability test for SCSORF-M has shown good Cronbach’s alpha (0.835). The SCSORF-M has positive correlation with NORA and IR (p-value 0.11 and <0.001 respectively). The positive correlation with OR is not statistically significant. Conclusion: Religiosity is an important factor to determine or intermediate the outcome of mental health among adolescents, and SCSORF is one of the reliable measurement tools to assess the religiosity distribution of a person.